Context-aware augmented reality in laparoscopic surgery - Katić, Darko; Wekerle, Anna-Laura; Görtler, Jochen; Spengler, Patrick; Bodenstedt, Sebastian; Röhl, Sebastian; Suwelack, Stefan; Kenngott, Hannes Götz; Wagner, Martin; Müller, Beat P.; Dillmann, Rüdiger; Speidel, Stefanie (Computerized medical imaging and graphics, 2013)
Augmented Reality is a promising paradigm for intraoperative assistance. Yet, apart from technical issues, a major obstacle to its clinical application is the man-machine interaction. Visualization of unnecessary, obsolete or redundant information may cause confusion and distraction, reducing usefulness and acceptance of the assistance system. We propose a system capable of automatically filtering available information based on recognized phases in the operating room. Our system offers a specific selection of available visualizations which suit the surgeon's needs best. The system was implemented for use in laparoscopic liver and gallbladder surgery and evaluated in phantom experiments in conjunction with expert interviews.